An Overview 0f Adolescent Knowledge Levels About Early Marriage in Class XII Teenagers at Smk Pencawan Bunga St. Ncole Raya Medan Tuntungan 2021 - Marta Dessy Sianturi; Risda Mariana Manik; Bernadetta Ambarita (Science Midwifery, 2022)
Early marriage or young marriage itself is a marriage carried out by a partner or one of their partners is still categorized as a teenager under the age of 19 year. The type of research used is descriptive with the Accidental Sampling method. The purpose of this study is to determine the level of knowledge of adolescents about early marriage, to find out the sources of information that affect adolescents' knowledge of early marriage, to determine ethnicity that affects adolescents' knowledge of early marriage. The samples in this study are 30 students of class 12 SMK Pencawan, by distributing questionnaires. The results obtains based on the level of knowledge of adolescents about early marriage in class XII adolescents at SMK Pencawan shows that the level of knowledge of adolescents about early marriage is the majority 15 people (50.0%) with good knowledge level criteria, while the minority had sufficient knowledge, namely 6 people (20.0%). Sources of information that influence adolescent knowledge about early marriage are the majority from the internet 15 people (50.0%), while the minority from print media 3 people (10.0%). The ethnic groups that influence adolescent knowledge about early marriage are 11 people (36.7%), while the least are the Simalungun, Gayo, Rao, Mandailing, Pakpak tribes each 1 person (3.3%). about early marriage, sources of information, and ethnicity, at SMK Pencawan good. However, it is hoped that in the future it will be even better